Cinematic artwork as a singularity: interviews with Noel Carroll - Denize Araujo; Fernão Ramos (Rebeca: Revista Brasileira de Estudos de Cinema e Audiovisual, 2018)
Interview with Noel Carroll, keynote speaker at the XX Socine Annual Meeting, on the cinematic artwork as a singularity.